Da hierarquização funcional à segregação do espaço urbano : uma análise da Vila Operadora de Estreito-SP - Liporone, Francis (2007)
Despite being independent from the housing market and its effects, the residential villages, built by companies linked with the productive and energetic sectors for their workers, has reproduced the fragmentation space typical from a city where the space conflicts are noticeable. It s the relation company/urban formation which states the singularity of these living sites which are found all over the national territory. The operating village (similar to a company town) of Estreito hydroelectric dam placed in the countryside of São Paulo state (Pedregulho municipality, microregion of Franca), undoubtly one of these cases, is the main objective focused on present study. The way that either main or general objective of the research is to understand, using analytical comparisons to other urban experiences of villages, the motivating processes for the production of a segregative space in the village of Estreito which belongs to Furnas Centrais Elétricas S/A. As a strategy of research, the study focus on the moment which the village of Estreito-SP was idealized and implanted, its original project, in other words, it was discussed the initial objectives of the creation of a village with segregative spaces and its main characteristics. So, the proceeding method adopted passed along and abstracted points of historical method looking for comprehension of the object on its time as well as its development. It was used not only survey applied at the residents of the village who has lived therefore more than twenty years, some informal notes but also the experience and living of the researcher in the location to reach the analytical description of the object. It was made a literary analysis tanging the thematic of social-spacial segregation and of the Company towns and its correlative as the operating villages in the first part of this dissertation. In the sequence descriptions and analysis of the empiric object,the village of Estreito by studying the calculated case in a descriptive and analytic history. To end the research there are the final considerations in which some indagations of research are answered such as the indication of main motivating factors to create a space which states the quality of life including the different living types is the attraction of qualified labor force to end the research.